Fancy Dress as an Amateur Craft. (2nd January 2020) - Knott, Stephen
Abstract : Starting from the author's own vexed relationship with fancy dress, this article explores the practice and social-cultural meaning of fancy dress in both historical and contemporary contexts. Fancy dress is positioned as an amateur craft that challenges the idea of amateur practice as necessarily self-expressive and its practitioners as repositories of affect. Academics in the fields of fashion history, design history and performance studies alike tend to frame amateur activity in a broadly celebratory light: as a location of self-expression, political autonomy and recuperative therapy. However, this article shows fancy dress to be a combination of personal expression and socio-cultural expectation that renders it more conventional, embarrassing, private and ambiguous than we might initially presume. The study focuses on the late nineteenth century, the era, as dress historians have identified (Mitchell 2017 ; Jarvis and Raine 1984 ), that witnessed the proliferation of the fancy dress ball as a respectable amusement, distinct from the frivolity and careless abandon of the Georgian masquerade. The article draws from late-nineteenth-century manual literature, advertisements and periodicals to explore the hints and tips that shaped the practice, with a particular focus on the extent to which people made their own garments or relied on the broader infrastructure of supply that made dressing up possible. This exploratory article aims to highlight the complex trajectories of amateur production through fancy dress, discussing its conformity, complicity in imperial notions of race, and ad hoc nature. This informs our understanding of debates about amateur practice today. The article concludes by considering the partial commitment to fancy dress through accessorizing as a metaphor for the amateur condition, reflecting an elastic relationship to everyday life that depends on but also stretches its structures.